The Influence of Social Assistance Expenditure, Education, and Unemployment on Poverty in Districts/Municipalities of D.I. Yogyakarta Province 2013-2022 - Yulida Wanda; Azansyah Azansyah (UNIVED Press, 2024)
This study aims to determine the effect of social assistance spending, education, and unemployment on poverty in 5 regencies/cities of D.I Yogyakarta Province in 2013-2022. The analysis method uses panel data regression. The time series data covers 2013-2022, and the cross-section data involves five districts/cities in D.I Yogyakarta Province. The selected model is the random effect model (REM). The results state that social assistance expenditure, education, and unemployment affect poverty in the districts/cities of D.I Yogyakarta Province 2013-2022.